Disaster Risk Education of Final Year High School Students Requires a Partnership with Families and Charity Organizations: An International Cross-sectional Survey. Issue 3 (29th March 2016) - Codreanu, Tudor A.; Celenza, Antonio; Ngo, Hanh
Abstract: Introduction: The aim of disaster reduction education (DRE) is to achieve behavioral change. Over the past two decades, many efforts have been directed towards this goal, but educational activities have been developed based on unverified assumptions. Further, the literature has not identified any significant change towards disaster preparedness at the individual level. In addition, previous research suggests that change is dependent on multiple independent predictors. It is difficult to determine what specific actions DRE might result in; therefore, the preamble of such an action, which is to have discussions about it, has been chosen as the surrogate outcome measure for DRE success. This study describes the relationship of the perceived entity responsible for disaster education, disaster education per se, sex, and country-specific characteristics, with students discussing disasters with friends and family as a measure of proactive behavioral change in disaster preparedness. Methods: A total of 3, 829 final year high school students participated in an international, multi-center prospective, cross-sectional study using a validated questionnaire. Nine countries with different levels of disaster exposure risk and economic development were surveyed. Regression analyses examined the relationship between the likelihood of discussing disasters with friends and family (dependent variable) and a series of independent variables. Results: There was no statistically significant relationship between a single entity responsible for disaster education and discussions about potential hazards and risks with friends and/or family. While several independent predictors showed a significant main effect, DRE through school lessons in interaction with Family & Charity Organizations had the highest predictive value. Conclusions: Disaster reduction education might require different delivery channels and methods and should engage with the entities with which the teenagers are more likely to collaborate. TA Codreanu, A Celenza, H Ngo .Disaster risk education of final year high school students requires a partnership with families and charity organizations: an international cross-sectional survey .Prehosp Disaster Med .2016 ;31 (3 ):242 –254 .